Facing Commercialism Within Optometry - Larsson, F (Canadian Journal of Optometry, 2021)
This paper Is actually the text of an address delivered by Professor Larsson to the 1985 Annual Meeting of the International Optometric and Optical League (IOOL). The Canadian Journal of Optometry's Managing Editor, Dr. Roland des Grosellliers, attended the IOOL meeting as Canada's official delegate and requested a copy of Professor Larsson's presentation.